2020
DOI: 10.1002/ccd.28850
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term clinical effects of recanalization of chronic coronary total occlusions in patients with left ventricular systolic dysfunction

Abstract: Objectives: The aim of the present analysis is to evaluate the clinical impact of chronic total occlusions (CTOs) recanalization in patients with left ventricular (LV) systolic dysfunction. Background According to contemporary knowledge, patient selection for percutaneous CTO revascularization is not yet standardized. In particular, data on outcomes in patients with LV systolic dysfunction undergoing percutaneous coronary intervention (PCI) for CTO are scarce. Methods: From a total of 2,421 consecutive patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
2
1
1
Order By: Relevance
“…The rate of TVR observed in our study was consistent with previously reported data, and TVR was the predominant determinant of MACE (19,40,41). In a recent study, Pinto et al reported that, in patients with LV systolic dysfunction, the TVR rate was 29.8% in revascularized CTO group and 15.5% in not revascularized CTO group (31). In addition, Galassi et al also reported, in CTO patients with low LVEF, the rate of TVR was 6.1% in successful CTO PCI group but 0% in failed CTO PCI group (32), which was consistent with our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The rate of TVR observed in our study was consistent with previously reported data, and TVR was the predominant determinant of MACE (19,40,41). In a recent study, Pinto et al reported that, in patients with LV systolic dysfunction, the TVR rate was 29.8% in revascularized CTO group and 15.5% in not revascularized CTO group (31). In addition, Galassi et al also reported, in CTO patients with low LVEF, the rate of TVR was 6.1% in successful CTO PCI group but 0% in failed CTO PCI group (32), which was consistent with our study.…”
Section: Discussionsupporting
confidence: 92%
“…Clinical outcomes between successful CTO PCI and MT (CTO-PCI not attempted) groups were investigated to better reflect the overall risk of patients with coronary CTO. Our study differs from previous studies (19,31) and is more reflective of the "real world" of clinical practice. To the best of our knowledge, this is the first large cohort study reporting on the long-term outcomes of successful recanalization compared to MT in unselected CTO patients with and without LV dysfunction.…”
Section: Discussioncontrasting
confidence: 62%
“…The existing literature has suggested an association between recanalization of chronic total occlusion (CTO) by percutaneous intervention and its beneficial effects on clinical outcomes. [1][2][3][4][5] Meanwhile, CTO percutaneous coronary intervention (PCI) has undergone a remarkable improvement in procedural success during the past two decades. 6 CTO secondary to in-stent restenosis (ISR) is not rare, and it is considered as a consequence of late thrombotic stenosis, in-stent atherosclerosis, or endothelium hyperproliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Пациенты с успешной реканализацией целевой ХОКА были отнесены к группе ХОКА-р, а пациенты с неудачной реканализацией или без неев группу ХОКА-н. При долгосрочном наблюдении пациенты группы ХОКА-н имели значительно более высокий уровень общей и сердечной смертности по сравнению с пациентами, с успешной ЧКВ, а сократительная функция миокарда увеличивалась в среднем на 11-17% [37]. По оценке итальянских коллег, ЧКВ при ХОКА было связано с явной клинической пользой и являлось прогностически благоприятным для пациентов старческого возраста.…”
Section: анализ результатов чкв при лечении хока пациентов старческог...unclassified